Lone Genius or Swarm Intelligence? Myths about Germany’s Sponsorship of Research Institutes - Powel, Justin; Baker, David (International Higher Education, 2021)
Countries around the world have emulated Germany’s model of the university devoted to research-based teaching. The independent, extra-university research institute led by a leading “genius” scientist was also developed in Germany. In recent decades, Germany’s research budget and science system continue to be split between its universities, which are relatively underresourced, and institutes enjoying favored sponsorship and significant funding. We argue that Germany could be even more productive with stronger support for the research university.